Research on the Mechanism of Surfactant Warm Mix Asphalt Additive-Based on Molecular Dynamics Simulation - Pinhui Zhao (MDPI AG, 2021)
Warm mix asphalt (WMA) technology can bring certain environmental and technical benefits through reducing the temperature of production, paving, and compaction of mixture asphalt. Recent studies have shown that some WMA additives are able to reduce the temperature by increasing the lubricating properties of asphalt binder-based on the tribological theory, this paper studied the mechanism of adsorbing and lubricating film of base asphalt and WMA on the surface of stone by molecular dynamics (MD) simulation method, and the effect of surfactant WMA additive on the lubrication performance of the shear friction system of “stone–asphalt–stone”. The model of base asphalt lubricating film, including saturates, aromatics, resin and asphaltene, as well as the model of warm mix asphalt lubricating film containing imidazoline-type surfactant WMA (IMDL WMA) additive molecule, were established. The shear friction system of “stone–asphalt–stone” of base asphalt and warm mix asphalt was built on the basis of an asphalt lubrication film model and representative calcite model. The results show that the addition of IMDL WMA additive can effectively improve the lubricity of asphalt, reduce the shear stress of asphalt lubricating film, and increase the stability of asphalt film. The temperature in the WMA lubricating film rises, while the adsorption energy on the stone surface decreases with the increase of shear rate, indicating that the higher the shear rate is, the more unfavorable it is for the WMA lubricating film to wrap on the stone surface. In addition, the shear stress of the WMA lubricating film decreased with increasing temperature, while the shear stress of the base asphalt lubricating film increased first and then decreased, demonstrating that the compactability of the asphalt mixture did not improve linearly with the increase of temperature.